2012
DOI: 10.1021/pr300798z
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Quantitative Protein Expression Profiling and MRM Verification of Markers in Type 2 Diabetes

Abstract: The pathogenesis of Type 2 diabetes mellitus (T2DM) is complex owing to molecular heterogeneity in the afflicted population. Current diagnostic methods rely on blood glucose measurements, which are noninformative with respect to progression of the disease to other associated pathologies. Thus, predicting the risk and development of T2DM-related complications, such as cardiovascular disease, remains a major challenge. We have used a combination of quantitative methods for characterization of circulating serum b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 77 publications
5
44
0
2
Order By: Relevance
“…Thus, plasma fibulin-1 appears as a new biomarker for vascular damage, which is in line with the results from four subsequent studies, where plasma fibulin-1 was found to be associated with diabetes, hypertension, and kidney damage (19)(20)(21). Interestingly, two of these studies used non-hypothesisdriven proteomic approaches to search for new markers (20,21). In the current study, we could confirm the previously observed associations between plasma fibulin-1 and age, glycemic status, and pulse pressure, although the correlations were not as strong as previously reported (18).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, plasma fibulin-1 appears as a new biomarker for vascular damage, which is in line with the results from four subsequent studies, where plasma fibulin-1 was found to be associated with diabetes, hypertension, and kidney damage (19)(20)(21). Interestingly, two of these studies used non-hypothesisdriven proteomic approaches to search for new markers (20,21). In the current study, we could confirm the previously observed associations between plasma fibulin-1 and age, glycemic status, and pulse pressure, although the correlations were not as strong as previously reported (18).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, plasma fibulin-1 concentrations independently predicted mortality in a 15-year follow-up period (18). Thus, plasma fibulin-1 appears as a new biomarker for vascular damage, which is in line with the results from four subsequent studies, where plasma fibulin-1 was found to be associated with diabetes, hypertension, and kidney damage (19)(20)(21). Interestingly, two of these studies used non-hypothesisdriven proteomic approaches to search for new markers (20,21).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…2) [37][38][39]. The best independent predictive apolipoproteins were Apo M, Apo D and Apo L1 (Tables 2 and 3); the performance of Apo M and Apo L1 depended on BMI grouping.…”
Section: Discussionmentioning
confidence: 95%
“…It is not immediately clear why extracellular proteins would localize intracellularly to LDs or why their localization would be affected by hepatic steatosis; however, many of the identifi ed extracellular proteins have links to hepatic steatosis, obesity, and diabetes (72)(73)(74)(75)(76). Additionally, it is not clear whether these extracellular proteins are in the secretory pathway or are being endocytosed.…”
Section: Discussionmentioning
confidence: 99%